Antimicrobial susceptibility patterns and empirical prescribing practices in adult in patients with urinary tract infection: is there a need for changing clinical practices? - CN Wijekoon; KMMP Dassanayake; A Pathmeswaran (Sri Lankan Journal of Infectious Diseases, 2014)
Introduction: Knowledge of local antimicrobial susceptibility is essential for prudent empiric therapy for urinary tract infection (UTI).The aim of this study was to describe antimicrobial susceptibility patterns and empirical prescribing practices in adult in patients with UTI. Methods: The study was carried out at a tertiary care hospital in Sri Lanka. Data was collected prospectively from consecutive adult in patients with positive urine culture and clinical features compatible with UTI. Sensitivity testing was done using Joan Stokes method. The etiological uropathogens, antibiotic susceptibility rates, association between antimicrobial susceptibility rates and background variables and empirical prescribing practices were analyzed. Results: 745 subjects were studied. Mean (SD) age was 48.2 (19) years and 441(59.2%) were females. Coliforms were the commonest isolates (85.6%). Overall, 76.8% of the isolates were susceptible to nitrofurantoin. (coliforms-74.9%; Streptococcus spp.-100%; Staphylococcus spp.-95.6%). Overall susceptibility was < 50%, to many antimicrobials. Among coliforms and pseudomonas isolates susceptibility to ciprofloxacin was 37.7% and 29.4% respectively.  The susceptibility rates of coliforms varied according to age, gender, origin of UTI and presence of co-morbidities. 381(51.1%) subjects received empirical antimicrobials. Ciprofloxacin was the most frequently prescribed empirical antimicrobial (208/381; 54.6%). Despite high susceptibility nitrofurantoin was prescribed in 9.2% only. Conclusions: Susceptibility was low to many first line and second line antimicrobials used to treat UTI in adults. There was obvious discrepancy between empirical prescribing practices and the susceptibility pattern of isolates. Incorporation of local surveillance data in to clinical practice will be useful to optimize the use of empirical antimicrobial therapy. DOI: http://dx.doi.org/10.4038/sljid.v4i1.6229